Fear or agitation as normative elements of the excess of necessary defense (Ius Novum, 2024)
The authors of this publication have explored the importance of justifying fear and agitation underlying the transgression of necessary defense. Pursuant to the provisions of art. 25 § 2 and 3 of the Penal Code they distinguished five situations, differing in the method of determining the mental state of the perpetrator, which translates into the criminal law consequences of unlawful infringement/exposure of the aggressor’s goods. Finally, verified the preliminary hypothesis, according to which the legislator initially assumed that exceeding the limits of necessary defense is caused by fear or agitation resulting from the circumstances of the attack, which, however, requires procedural confirmation. Their occurrence leads to impunity of the defender, regardless of the type of legal interests infringed by him and the degree of exceeding the limits of necessary defense. A deficit in the circumstances of the mental state of a defender referred to in Art. 25 § 3 of the Penal Code in a specific factual state, it opens the possibility of applying a general – complementary provision, i.e. the provision of Art. 25 § 2.
Keywords: criminal law, justification, self-defense, self-defense excess, fear and agitation